Pengembangan Instrumen Tes Berbasis Daring untuk Mengukur Keterampilan Inkuiri Ilmah Siswa pada Materi Suhu dan Kalor - Yunita, Maya Septian; Wiyanto, Wiyanto (UPEJ Unnes Physics Education Journal, 2021)
Scientific Inquiry skills are the ability to make discoveries based on facts or phenomena that exist through the observation process based on the stages of inquiry. Based on literature studies, research discussing the development of scientific instruments of inquiry skills tends to be published in international journals rather than national journals that are more likely to discuss the skills of the scientific process. This study aims to develop online-based instruments to measure students' scientific inquiry skills on temperature and heat materials that are valid, reliable and practical. The method applied is a research and development (R &D) method with a 4-D development model that has been modified to 3-D. The research trial was conducted on XI grade students at SMA Negeri 1 Jakenan. The results of the expert validity test by expert judgment. show the average score above 80% with a very valid category. A wide-scale trial of 227 students to obtain the validity of the construct, reliability and practicality of the instrument. The test of the validity of the construct with confirmatory factor analysis assisted by using Software Lisrel 8.80 get in 13 items out of 19 question items that developed in a valid category and able to represent each construct theory of scientific inquiry skills. The instruments developed have strong reliability which is indicated by a score of 0,78. The instrument is rated practical by students with a score of 3,23 from 4.00 and it is rated very practical by teachers with a score of 3.6 form 4.00. Based on the results of the test, the instrument developed is proper to be used for measuring student’s scientific inquiry skills.